2020
DOI: 10.1021/acsmacrolett.0c00404
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Isotropic–Nematic Transition in Poly(ether ether ketone) Melts

Abstract: In a previous work on a poly(ether ether ketone) (PEEK) melt, above

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…With W > 50 MPa, strong viscosity (or shear stress) fluctuations are monitored presumably due to dynamic motions of polydomain PEEK nematic directors. 32 For low shear rates of γ̇< 5 s −1 at T s = 328 °C, the strong viscosity fluctuations cannot be observed since the onset of crystal growth occurs before reaching W ∼ 50 MPa.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…With W > 50 MPa, strong viscosity (or shear stress) fluctuations are monitored presumably due to dynamic motions of polydomain PEEK nematic directors. 32 For low shear rates of γ̇< 5 s −1 at T s = 328 °C, the strong viscosity fluctuations cannot be observed since the onset of crystal growth occurs before reaching W ∼ 50 MPa.…”
Section: Resultsmentioning
confidence: 98%
“…Parisi et al 32 have recently observed a nematic phase of PEEK in shear flow by monitoring the birefringence and instability of shear flow using an optical rheometer. With rheology, the existence of a flow-induced nematic phase was verified from uncorrelated fluctuations of shear flow that are attributed to the diverse dynamic motions of polydomain nematic directors, such as tumbling, wagging, log-rolling, or kayaking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further extensional flow studies on the poly-alkyl isocyanates and other stiff-chain polymers are currently underway where the influence of solvent, temperature and solution concentration is being investigated, especially at higher concentrations as it is suggested that extensional flow would induce an isotropic-to-liquid crystal transition reported in shear flow in relatively rigid polymer chains 42,43 and may explain the spider silk web processing. 44,45 4 | CONCLUSIONS This investigation showed that the transient extensional response of stiff-chain polymers is rather complex, suggesting multiple macromolecular orientation changes.…”
Section: Resultsmentioning
confidence: 99%
“…Semiflexible LCPs enabled the fundamental understanding of shear‐induced isotropic‐to‐nematic transition where highly aligned structures appeared as precursors of the nematic order 14 . Recently, the detection of a shear‐induced isotropic‐to‐nematic transition in the flexible chain poly(ether ether ketone) (PEEK) was reported, thus suggesting that the nematic phase may represent the early stage of the formation of shear‐induced crystallization precursors 15 …”
Section: Introductionmentioning
confidence: 99%